Root and tuber crops in Guyana - Forde, B.J. (International Center for Tropical Agriculture, 1986)
In Guyana, cassava is the most important root crop; root crops occupy the 5th place of importance in national food crop production. The main cropping systems used by the farmers in the different regions of the country are described. More than 1 crop is planted to reduce risks; in the Pomeroon region, cassava is planted as an intercrop with tree crops such as citrus, avocado, and other mixed fruits. The lowest price was paid for cassava. Although the domestic demand for root and tuber crops is primarily as fresh food, cassava is also consumed processed (flour, starch, cassareep, bread). Since 1970 the government of Guyana has restricted the importation of energy-rich agricultural products; therefore, they have been replaced with locally produced root and tuber crops. During this same period, the Accelerated Production Drive program was started; its objective was to promote cassava production and its processing into flour and animal feed. Unfortunately, the program was not successful. The staff of the National Research Institute is listed; research has focused mainly on rice and cassava. The results of research carried out on root crops are briefly presented, and for cassava, it is proposed to continue the evaluation of cv. and to study the different cropping systems. (CIAT)